In vitro propagation of Ananas comosus L. Merr. (Morris) - Hashimah, Elias; R.M., Taha; Hamsawi, Sani; N.F., Khamarul Huda; B.A., Ahmed; S., Abdullah; S.A., Zakeri (ISHS, 2021)
Ananas comosus L. Merr. (Morris) commonly known as pineapple, is an economically important fruit in Malaysia. Among the pineapple producers in the world, Malaysia has put massive efforts to fulfill the high domestic and global market demand. Several attempts have been made recently by integrating biotechnology in conventional breeding concerning issues on the shortage production of pineapple fruits. The fruit productivity could be enhanced via a tissue culture system as it might provide the good quality of planting materials in industrial scale throughout the years. Hence, this study was designed to assess the effectiveness of utilizing tissue culture technique to produce sufficient plantlets of pineapple. The procedure involved culturing aseptic axillary buds excised from suckers in treatments with various concentrations of 6-benzylamino purine (BAP) to induce shoot multiplication. The suckers were successfully disinfected by soaking in 100% Clorox for 3 min with 80% survival and free contamination. The best result for this experiment was obtained in MS supplemented with 3.0 mg L-1 BAP, produced the highest no. of shoots per explant with the highest no. of leaves per explant. Besides, it was found that the treatments added with more than 3.0 mg L-1 BAP decreased the number of shoots and leaves per explant. Nevertheless, further advance study especially in quality control should be done to verify the quality of fruits meet the standard for commercialization.